The role of strategic intelligence in enhancing organizational performance (Exploratory research of the opinions of the administrative leadership of the University of Fallujah) - فائق, تلا عاصم; عبد, عذراء محسن (Journal of Economics and Administrative Sciences, 2018)
The main idea of ​​this research stems from the challenges faced by managers working in service organizations, which are responsible for providing services to a large segment of the society. Therefore, they must use strategic intelligence to manage their performance and enhance their performance to serve the society. Organizational Performance The present study aimed to identify the concepts of strategic intelligence and its impact on organizational performance to raise awareness and awareness of the importance of the subject for the university. And to identify the perceptions of leaders about strategic intelligence and determine the nature of the relationship (impact and correlation) between strategic intelligence and organizational performance and finally make recommendations that would activate the role of strategic intelligence in enhancing the organizational performance and applied this research to a vertical sample, 80), the head of university 1, the vice president of the university 2, the deans 5, the assistant dean 10, the head of the department or the branch 35, Managers of divisions and units 27) In order to process the data and information, The study concluded that A number of conclusions, including that strategic intelligence in all its dimensions and components contribute effectively to enhance organizational performance and provide the strategic intelligence of the leaders in question contributes to the achievement of the goals of the University and its colleges. Also, the vision of the administrative leaders at Fallujah University about its employees are unified towards the development of the university in all aspects and fields, The University is committed to motivating the employees who achieve the highest achievement rates and perform their duties as required. The study contributed a set of recommendations, including attention to strategic intelligence for the organizations To the General Service because of its impact on its organizational performance and also attention to the development of future plans and also attention to the work teams for their positive impact on the performance of the Organization.